Kemampuan Literasi Media Siswa di SMAN 1 Lubuk Sikaping Berbasis Individual Competence Framework - Notfel, Deni; Nelisa, Malta (Scinary, 2023)
This research examines the media literacy abilities of students at SMA Negeri 1 Lubuk Suhuing. The aim of this research is to explain students' abilities in using media, understanding media, analyzing, evaluating and producing information in the media. The location of the research was at SMA Negeri 1 Lubuk Suhuing Jl. M Yamin No.2, Lubuk Suhuing, Pauah, Pasaman, Pasaman Regency, West Sumatra.This research uses quantitative research with descriptive methods. The population in this study were students at SMA Negeri 1 Lubuk Suhuing with samples taken using simple random sampling. The main instrument used was a research questionnaire which had been tested for validity and reliability, the sample size was 92 people. Data collection techniques are questionnaire techniques and questionnaire data processing through editing and tabulation stages.The results of the research are: the Use Skill indicator (technical ability) has an average score of 3.41 which is on an interval scale of 3.25 – 4.00 so it can be concluded that the technical ability of students at SMA Negeri 1 Lubuk Suhuing is categorized as very good. The Critical Understanding indicator has an average score of 3.47 which is on an interval scale of 3.25 – 4.00 so it can be concluded that the critical understanding of students at SMA Negeri 1 Lubuk Suhuing is in the very good category. the Communicative Ability indicator (communicative ability) has an average score of 3.16 which is on an interval scale of 2.50 – 3.24 so it can be concluded that students at SMA Negeri 1 Lubuk Suhuing have communicative abilities in the good category. The Evaluation and Analysis indicator has an average score of 3.15 which is in the interval score of 2.50 – 3.24, so it can be concluded that the ability to evaluate and analyze the information of SMA Negeri 1 Lubuk Suhuing students is in the good category.